Brief focal psychoanalytic psychotherapy. A modality of intervention for university students: "ESPORA Psychological" - Janett Esmeralda Sosa Torralba; Bertha Blum Grynberg; Catalina Elizabeth Stern Forgach; José Vicente Zarco Torres (Interacciones)
Background: The current individual and socio-cultural conditions of subjects require technical adaptation in the modalities of psychotherapeutic treatment. In this article, we present a psychotherapy brief focal psychoanalytic model for young people adapted to their university context. We begin by describing the characteristics of brief psychoanalytic psychotherapy and the peculiarities of the transition of young people entering the university environment who deal with situations that cause emotional tension and distress. In the second section, the model is described, both in its theoretical and technical foundations. Method: Theoretical review. Conclusion: We consider the usefulness of implementing the model in an educational center with university students and it is concluded that, by analyzing and solving their problems with the psychotherapy used, it will allow them to represent their experiences in a different way and make changes in them.